2022
DOI: 10.3390/polym14030385
|View full text |Cite
|
Sign up to set email alerts
|

Improved Dielectric Breakdown Strength of Polyimide by Incorporating Polydopamine-Coated Graphitic Carbon Nitride

Abstract: Breakdown strength is an important parameter for polymer dielectric, and introducing inorganic filler into the polymer matrix is an efficient method to improve the breakdown strength. In this work, graphitic carbon nitride nanosheets (CNNS) were ultrasonically exfoliated and coated with polydopamine to obtain modified nanosheets (DCNNS), and then polyimide (PI) composite films with various CNNS and DCNNS were prepared and compared. Owing to the abundant hydroxyl groups of polydopamine, good filler-polymer comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 34 publications
(37 reference statements)
0
20
0
Order By: Relevance
“…The enhancement of breakdown strength is usually related with the properties of filler and interfacial coupling between fillers and matrix. 5 modified film was higher than that of pure PI film. 6 Guo et al prepared PI/SiO 2 composite film with a weight fraction of 10% of SiO 2 , and they demonstrated that the corona resistance time and conductivity were greatly improved compared with those of the pure PI film.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…The enhancement of breakdown strength is usually related with the properties of filler and interfacial coupling between fillers and matrix. 5 modified film was higher than that of pure PI film. 6 Guo et al prepared PI/SiO 2 composite film with a weight fraction of 10% of SiO 2 , and they demonstrated that the corona resistance time and conductivity were greatly improved compared with those of the pure PI film.…”
Section: Introductionmentioning
confidence: 76%
“…The breakdown strength of PI films can be effectively improved by adding nanofillers into the PI matrix. The enhancement of breakdown strength is usually related with the properties of filler and interfacial coupling between fillers and matrix . For instance, Harrison et al doped silica dioxide (SiO 2 ) nanoparticles into PI with a gradient weight fraction and found that the breakdown strength of the modified film was higher than that of pure PI film .…”
Section: Introductionmentioning
confidence: 99%
“…According to national standard GB/T 1408.1-2006, the relationship between the tensile stress and the insulation properties of the material was investigated by subjecting four groups of polyethylene specimens with different elongation ratios to a frequency AC breakdown test. The experimental electrode is a spherical electrode with a diameter of 25 mm, and the polyethylene breakdown experimental setup is shown in Figure 1 [ 20 , 21 ]. The voltage is increased to 15 kV and then the voltage is increased at a constant rate until the sample breaks down.…”
Section: Methodsmentioning
confidence: 99%
“…79 It may be that the submicron thickness of the film, as well as the change in film roughness, allows the leakage current to have only a small change when the porosity increases. In addition, the breakdown field strength of these organic films is higher than that of pure polyimide (PI) films (∼1.79 MV/cm), 77 which are known to be widely used as dielectric materials in the field of electronics.…”
Section: Dielectric and Electricalmentioning
confidence: 99%